INFLUENCE OF LEADERSHIP AND ORGANIZATION CLIMATE ON EMPLOYEE PERFORMANCE - Abas, Muhammad; Isyanto, Puji; Rachmawati, Mariana (International Journal of Psychosocial Rehabilitation, 2020)
This Research aims to test and analyze the influence of leadership and climate of the Organization on the performance of employees PT Cipta Kreasi Wood Industry Karawang. Data collection is taken based on employee data that works at PT. Cipta Kreasi Wood Industry Karawang established a population of 230 people with a sample amount of 146 people. The variables examined are two free namely the leadership and climate of the Organization, as well as one binding variable i.e. employee performance. This type of research is quantitative. Research data retrieval techniques using poll or questionnaire techniques